A decision support system for determining Corporate Social Responsibility (CSR) fund recipients using the dead method (Case study: PT. Ukindo Blankahan Estate) - Andika, Rio; Maulita, Yani; Syahputra, Suria Alam (Journal of Engineering, Technology and Computing (JETCom), 2025)
Corporate Social Responsibility (CSR) is a form of a company’s social responsibility to the community. PT. UKINDO Blankahan Estate faces challenges in determining CSR aid recipients because the selection process is still conducted manually, making it prone to subjectivity.This study aims to develop a Decision Support System (DSS) for determining CSR aid recipients using the Multi-Attribute Utility Theory (MAUT) method with five main criteria: location distance, proposal type, amount of funds, impact scale, and proposal value. The system was designed as a web application using PHP and MySQL.The results show that the system can automatically perform normalization, weighting, and ranking processes. In the case study of proposals for the Maulid Nabi commemoration, the highest rank was obtained by Desa Blankahan with a score of 0.71460, while the lowest rank was obtained by PRM Al-Amin with a score of 0.19170. This system proves effective in assisting the company to select CSR aid recipients more objectively, efficiently, and accurately.